The Effect of Ball Heading and Subclinical Concussion On the Neuromuscular Control Of The Lower Limb: A Systematic Review - Georgios Kakavas; Ioannis Giannakopoulos Sr.; Athanasios Tsiokanos; Michael Potoupnis; Panagiotis V. Tsaklis (International Journal of Sports Physical Therapy)
# Background